Establishing a University Writing Center: A Lesson Learned from Universities Outside Nepal - Pandey, Hem Lal (SCHOLARS: Journal of Arts & Humanities, 2024)
The goal of this article is to characterize the university writing center as a crucial institutional resource for the support of student writers and to advocate for its establishment at Tribhuvan University (TU). To achieve this, it explores the factors that prompted its origin and development in the universities of the United States of America. It also unpacks the underlying philosophy of the center by elucidating its pedagogical approaches, current practices, and administrative mechanisms. Building upon the historical contexts of writing centers, it proposes the establishment of a similar center at TU as a means to address the everyday concerns, needs, support, and assistance of the community of student writers within the university domain. Furthermore, it investigates the types and ways of potential academic opportunities that a writing center can provide to enhance effective writing skills and publishing practices in the university. Through a review of the historical as well as pedagogical practices of writing centers in the United States, the article establishes its argument that introducing a writing center at TU can contribute to various forms of support, such as source identification, audience awareness, review and feedback, documentation, etc., catering to writers of all levels, from novices to experienced, in developing their writing skills, habits, and practices. Additionally, the proposed writing center at TU is positioned not only as a productive student support system for a resourceful learning environment but also as a space offering on-campus employment opportunities for students, ultimately fostering a stronger connection between academia and the job market.